Applying Business Model on Product Development Case of Xinshe Farm - Ke, Wang (International Journal of Management and Education in Human Development, 2022)
In launching a new product development and launch process for Xinshe Farm, a company that offers fresh produce from its farm to the consumer public. The objective of this paper is to develop a framework for the entire product development and launch process and increase the success rate in the future in the new normal of new product launches. His personal experiences and reviews of the literature, business cases, journals, and data analysis are the foundation of the new product launch model.